2003
DOI: 10.1196/annals.1284.045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relaxing Music on Salivary Cortisol Level after Psychological Stress

Abstract: The goal of the present study was to determine whether relaxing music (as compared to silence) might facilitate recovery from a psychologically stressful task. To this aim, changes in salivary cortisol levels were regularly monitored in 24 students before and after the Trier Social Stress Test. The data show that in the presence of music, the salivary cortisol level ceased to increase after the stressor, whereas in silence it continued to increase for 30 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
189
2
21

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 5 publications
12
189
2
21
Order By: Relevance
“…Music is a powerful tool in evoking emotions and, by extension, listening to music can be explored for reducing the negative effects of stress. Supportive evidence can be found in the observation that listening to music resulted in a marked reduction in salivary cortisol levels in patients exposed to pre-surgical stress, both in a medical (Miluk-Kolasa et al, 1994) and in a nonmedical setting (Khalfa et al, 2003). These experiments suggested that relaxing music is more effective than silence in decreasing cortisol levels after stress induction.…”
Section: Introductionmentioning
confidence: 82%
“…Music is a powerful tool in evoking emotions and, by extension, listening to music can be explored for reducing the negative effects of stress. Supportive evidence can be found in the observation that listening to music resulted in a marked reduction in salivary cortisol levels in patients exposed to pre-surgical stress, both in a medical (Miluk-Kolasa et al, 1994) and in a nonmedical setting (Khalfa et al, 2003). These experiments suggested that relaxing music is more effective than silence in decreasing cortisol levels after stress induction.…”
Section: Introductionmentioning
confidence: 82%
“…Especially during stress, music has a positive effect on the constitution of the stressed individual [2] and may even be used prophylactically prior to negative, stress-induced reactions [3]. This positive effect can not only be evaluated with the aid of subjective parameters, but also objectively by applying physiological parameters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Outro importante estudo dos efeitos relaxantes da música foi realizado por Khalfa, Dalla-Bella, Roy, Peretz e Lupien (2003) Khalfa et al (2003) sugerem, a partir disso, que músicas que comportam disparidades de ritmo e dissonâncias podem ser estressantes. Segundo a hipótese de Khalfa et al (2003), passado o evento de estresse, uma música caracterizada pela lentidão, regularidade de tempo e harmonia ativa o córtex auditivo juntamente com outras estruturas implicadas no trato das emoções, reduzindo a atividade do complexo amigdalóide, parando de liberar o cortisol e inibindo toda a cadeia de reações.…”
Section: Introductionunclassified
“…Segundo a hipótese de Khalfa et al (2003), passado o evento de estresse, uma música caracterizada pela lentidão, regularidade de tempo e harmonia ativa o córtex auditivo juntamente com outras estruturas implicadas no trato das emoções, reduzindo a atividade do complexo amigdalóide, parando de liberar o cortisol e inibindo toda a cadeia de reações. A música pode proporcionar assim, uma sensação de bem-estar e alívio, cortando a cadeia de reações que ocorre devido a um evento estressante.…”
Section: Introductionunclassified
See 1 more Smart Citation